Anthropometric Measures and the Risk of Endometrial Cancer, Overall and by Tumor Microsatellite Status and Histological Subtype - Amankwah, Ernest K. (Oxford University Press, 2013)
Obesity is an established risk factor for endometrial cancer, but this association is not well understood for subtypes of endometrial cancer. We evaluated the association of recent and adult-life obesity with subtypes of endometrial cancer based on microsatellite status (microsatellite-stable (MSS) vs. microsatellite-instable (MSI)) and histology (type I vs. type II). Analyses were based on a population-based case-control study (524 cases and 1,032 controls) conducted in Alberta, Canada (2002–2006) and included the following groupings of subtypes: MSS = 337 and MSI = 130; type I = 458 and type II = 66. Logistic and polytomous logistic regression were used to estimate odds ratios and 95% confidence intervals for overall endometrial cancer and subtypes of endometrial cancer, respectively. The risks of all subtypes of endometrial cancer, except type II, increased with an increase in all of the anthropometric characteristics examined. The risks for MSI tumors were suggestively stronger than those for MSS tumors; the risk with high (≥30) body mass index (weight (kg)/height (m)(2)) was significantly stronger for MSI tumors (odds ratio = 4.96, 95% confidence interval: 2.76, 8.91) than for MSS tumors (odds ratio = 2.33, 95% confidence interval: 1.66, 3.28) (P-heterogeneity = 0.02). Obesity is associated with most subtypes of endometrial cancer, and further studies are warranted to elucidate the biological mechanisms underlying the stronger risk for the MSI subtype with a high body mass index.